3D Morphometry of the Acetabulum: Implications for Hip Replacement Surgery - Anwar, Kashif; Jagdeesh, Jagdeesh; Ullah, Zia; Khan, Hisham; Aliuddin, Akram Muhammad; Ali, Syed Danish (Journal of Neonatal Surgery, 2024)
Background: To evaluate the three-dimensional morphometric parameters of the acetabulum in an adult population and to determine differences based on gender and side. Methods: A cross-sectional study was conducted from May 2023 to May 2024, including 71 adults who underwent pelvic CT scans for non-orthopedic indications. Three-dimensional reconstructions were analyzed to measure acetabular diameter, height, depth, volume, version, inclination, and center–edge angle. Data were compared between genders and sides using appropriate statistical tests, with p < 0.05 considered significant. Results: The mean acetabular diameter was 52.8 ± 3.6 mm, height 47.5 ± 3.2 mm, and depth 25.4 ± 2.1 mm. The average version angle was 19.6 ± 4.8°, inclination 42.3 ± 5.2°, and center–edge angle 32.7 ± 5.1°. Males had significantly larger diameters, heights, and depths than females (p < 0.05), but no significant gender differences in version or inclination. No statistically significant side-to-side differences were observed. Conclusion: The acetabulum in this population shows gender-specific variations in size but similar orientation and bilateral symmetry. These findings underscore the importance of incorporating population-specific morphometric data into preoperative planning for hip replacement surgery..